The Effect of Augmented Reality-based Learning Technology on Improving Student Motivation and Learning Outcomes in Secondary Schools - Aulia Pratama; Budi Santoso (International Journal of Educational Insights and Innovations, 2024)
The integration of Augmented Reality (AR) in education has emerged as a promising approach to enhance learning experiences by making content more interactive and engaging. This study investigates the impact of AR-based learning technology on student motivation and learning outcomes in secondary schools. Using a quasi-experimental design, 120 students were divided into an experimental group, which used AR tools, and a control group, which received traditional instruction. Results showed that students in the experimental group demonstrated significant improvements in both academic performance and motivation compared to the control group. The study highlights the potential of AR technology to transform traditional teaching methods and suggests that AR can be a valuable tool in fostering deeper understanding and sustained interest in learning. These findings provide insights into the effectiveness of AR in educational settings and underscore the need for further research to explore its long-term impact and broader applications.